Research challenges in prehospital care: the need for a simulation-based prehospital research laboratory - Maurin Söderholm, Hanna (Adv Simul (Lond), 2019)
There is a need for improved research in the field of prehospital care. At the same time, there are many barriers in prehospital research due to the complex context, posing unique challenges for research, development, and evaluation. The present paper argues for the potential of simulation for prehospital research, e.g., through the development of an advanced simulation-based prehospital research laboratory. However, the prehospital context is different from other healthcare areas, which implies special requirements for the design of this type of laboratory, in terms of simulation width (including the entire prehospital work process) and depth (level of scenario detail). A set of features pertaining to simulation width, scenario depth, equipment, and personnel and competence are proposed. Close tailoring between these features and the prehospital research problems and context presents great potential to improve and further prehospital research.